Effectiveness of Gestalt-oriented and self-concept enhancement programs in developing achievement motivation of high school students: A comparative study - Sihombing, Junian Sahala Maringan Tua (Animo Repository, 1987)
This experimental study was undertaken to find out and compare the effectiveness of Gestalt-oriented and self-concept enhancement program in developing achievement motivation of high school students in the 16-17 age group. Specifically this study attempted to answer the following questions: 1. Is there a significant difference between the achievement motivation pretest and posttest scores as measured by the trait survey of: a) experimental group 1 (Gestalt-oriented program) b) experimental group 2 (self-concept enhancement program) c) control group 2. Is there a significant difference between the achievement motivation posttest scores as measured by trait survey of: a) experimental group 1 (GOP) and experimental group 2 (SCEP) b) experimental group 1 and control group c) experimental group 2 and control group 3. Is there a significant difference between the self-concept posttest scores of experimental group 1 (GOP) and experimental group 2 (SCEP) as measured by Pasao self-concept rating scale? The subjects were 34 fourth year high school students who were low in achievement motivation as measured by the Trait Survey. They were assigned randomly to three groups: the experimental groups, Gestalt oriented program (GOP) and self-concept enhancement Program (SCEP), who underwent a 12 hours training programs, and the Control Group did not. Two instruments were used: Trait Survey constructed by Mattakotil (1976) and de Sousa (1977) Pasao self-concept ratings constructed by Myrna Pasao (1979). The Pasao self-concept rating scale was given to know whether there was a significant difference between the self concept posttest scores of Experimental Group 1 (GOP) and Experimental Group 2 (SCEP).The data were treated by the use of t-test and Ancova. To find out a significant difference between the pretest and posttest results of the experimental and Control groups, the t-test for correlated samples was used. To find out a significant difference between the achievement motivation posttest scores of the two ex